Penerapan Tax Planning Atas Pajak Penghasilan Badan pada CV. Wira Arya Sejahtera - Dina Putri Nadiati; Syamsul Bahri Arifin (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2026)
This study aims to examine the implementation of tax planning for Corporate Income Tax at CV Wira Arya Sejahtera to legally reduce the tax burden in accordance with tax regulations. The approach used is a descriptive qualitative with a case study method. The data analyzed comes from the financial statements and Annual Tax Returns (SPT) of CV Wira Arya Sejahtera in 2023. The results of the analysis show that the implemented tax planning strategy is able to reduce the amount of Taxable Income (PKP), so that the amount of PPh payable can be reduced from Rp 200,119,828 to Rp 182,731,896. Thus, the company succeeded in achieving tax efficiency of Rp 17,387,933. The implementation of tax planning has a positive impact on tax efficiency and helps improve the company's financial condition. This shows that good tax planning can help companies optimize their tax obligations, increase cash flow, and create long-term benefits for the sustainability of their operations.